SOCIAL AND PSYCHOLOGICAL SUPPORT OF UKRAINIAN REFUGEES IN GREAT BRITAIN - Maiia Halytska; Yuliia Hryshchuk (Неперервна професійна освіта: теорія та практика)
The article presents an analytical report on the survey results of Ukrainian refugees concerning various aspects of their lives in the United Kingdom, with the aim of identifying priority areas for support. The questionnaire developed for the study is divided into two parts: the first part includes demographic characteristics (such as gender, age, educational level, employment status, and proficiency in English), while the second part consists of questions designed to examine different aspects of the refugees’ lives.